FinTech and MSMEs: The role of product knowledge - Majid, Rifaldi; Mawaddah, Herti (Faculty of Business & Economics, Universitas Islam Indonesia, 2022)
Purpose − This study examines the effect of knowledge of Islamic FinTech products and services of Micro, Small, and Medium Enterprises (MSMEs) actors on their intentions to adopt it.Methodology − This study adopts a quantitative method with primary data filled in by MSME actors in Indonesia. A hundred samples were analyzed using Partial Least Square - Structural Equation Modeling (SEM) by SmartPLS software.Findings − The results showed that both Perceived Usefulness (PU) and Perceived Ease of Use (PEoU) were empirically proven to have a significant positive effect on Attitude Toward Behavior (ATB). Likewise, ATB has been proven to be significant in mediating PU and PEoU on the Behavioral Intention (BI) of MSME actors in using Islamic FinTech products and services. The main finding in this research is that the higher the knowledge/literacy of Islamic finance by MSMEs, the more they will strengthen their intention to use FinTech products.Implications − The socialization of Islamic FinTech products and services by regulators such as the Financial Services Authority through collaboration with the industry players, professional and expertise organizations, the Muslim entrepreneur community, and universities need to be continuously to improve Islamic financial literacy. In addition, amid ongoing business digitalization, MSMEs are expected to be integrated with FinTech, not only in terms of funding but also in improving business performance regarding operations, finance, human resources, and others.Originality − This paper extends TAM with product knowledge on objects in the form of MSME actors in Indonesia.